Optimization of the current self-assembled urinary bladder model: Organ-specific stroma and smooth muscle inclusion - Orabi, Hazem; Rousseau, Alexandre; Laterreur, Véronique; Bolduc, Stéphane (Canadian Urological Association Journal, 2015)
Introduction: Due to the complications associated with the use of non-native biomaterials and the lack of local tissues, bioengineered tissues are required for surgical reconstruction of complex urinary tract diseases, including those of the urinary bladder. The selfassembly method of matrix formation using autologous stromal cells obviates the need for exogenous biomaterials. We aimed at creating novel ex-vivo multilayer urinary tissue from a single bladder biopsy. Methods: After isolating urothelial, bladder stromal and smooth muscle cells from bladder biopsies, we produced 2 models of urinary equivalents: (1) the original one with dermal fibroblasts and (2) the new one with bladder stromal cells. Dermal fibroblasts and bladder stromal cells were stimulated to form an extracellular matrix, followed by sequential seeding of smooth muscle cells and urothelial cells. Stratification and cellular differentiation were assessed by histology, immunostaining and electron microscopy. Barrier function was checked with the permeability test. Biomechanical properties were assessed with uniaxinal tensile strength, elastic modulus, and failure strain. Results: Both urinary equivalents could be handled easily and did not contract. Stratified epithelium, intact basement membrane, fused matrix, and prominent muscle layer were detected in both urinary equivalents. Bladder stromal cell-based constructs had terminally differentiated urothelium and more elasticity than dermal fibroblasts-based equivalents. Permeation studies showed that both equivalents were comparable to native tissues. Conclusions: Organ-specific stromal cells produced urinary tissues with more terminally differentiated urothelium and better biomechanical characteristics than non-specific stromal cells. Smooth muscle cells could be incorporated into the selfassembled tissues effectively. This multi-layer tissue can be used as a urethral graft or as a bladder model for disease modelling and pharmacotherapeutic testing.